CHARACTERISTICS OF FUELS AND FIRE RISK AMONG THE MAIN FOREST TYPES IN HOANG LIEN NATIONAL PARK - Minh Canh, Tran; Thai Son, Le; Xuan Thang, Le (Journal of Forestry Science and Technology, 2020)
Hoang Lien National Park has 25,113.66 ha of forest under its management, including the main forest types as natural broadleaf evergreen forest (poor; average and rehabilitation forests), bamboo, bamboo and mixed forests, and plantation forest. There are small areas of natural rich forest left, mainly located in strictly protected zone, and 2,143.75 ha of uncovered land or area of regenerating woody plants. There are clear differences in terms of fuels among forest types that were clarified by using indicators as trunk height, height and cover of understory vegetation, load and moisture of fuels. From the characteristics of fuels, the study divided fire risk for forests, shrublands and grasslands into 4 levels of danger. As a result, shrubs and grasses and bamboo forest are at highest fire risk (level IV); Plantation forest and evergreen poor forest are at high risk of fire (level III); Rehabilitation forests are at medium risk (level II); and evergreen average and rich forests are at low risk (level I). From the results above, this study also has created a map of fire risk division for forest types in Hoang Lien National Park.